THE LEARNING RESPONSIBILITIES OF JUNIOR HIGH SCHOOL STUDENTS: THE CORELATION OF DEMOCRATIC PARENTING AND SELF-REGULATION LEARNING - Ulaita Aliyatul Himmah; Wiwik Juwarini Prihastiwi (Archetype : Jurnal Ilmiah Psikologi dan Terapan, 2025)
This study aims to determine the effect of democratic parenting and self-regulated learning on the learning responsibilities of junior high school students. In addition, it is necessary to know which variables have the greatest influence on learning responsibilities. The sample of this study was 115 junior high school students from various junior high schools in East Java Province. The measuring instrument used to collect data was a scale arranged according to the dimensions of responsible learning behavior, democratic parenting, and self-regulated learning using a Likert scale model. The data analysis method used multiple regression, and the study results showed a significant influence between democratic parenting and self-regulated learning on the learning responsibilities of junior high school students (R = 0.773; p <0.005). The democratic parenting and self-regulated learning variables contributed 59.7% to the variation in the learning responsibility variable. The effective contribution of the self-regulated learning variable (53.49%) was greater than the effective contribution of the parenting variable to learning responsibilities (6.99%). Keywords: responsibility learning, democratic parenting, self-regulation learning. Keywords: learning responsibility, democratic parenting, self-regulated learning.